2013
DOI: 10.1007/s00125-013-2899-8
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of sweet beverages and type 2 diabetes incidence in European adults: results from EPIC-InterAct

Abstract: Aims/hypothesis Consumption of sugar-sweetened beverages has been shown, largely in American populations, to increase type 2 diabetes incidence. We aimed to evaluate the association of consumption of sweet beverages (juices and nectars, sugarsweetened soft drinks and artificially sweetened soft drinks) with type 2 diabetes incidence in European adults. Methods We established a case-cohort study including 12,403 incident type 2 diabetes cases and a stratified subcohort of 16,154 participants selected from eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
110
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(130 citation statements)
references
References 28 publications
(47 reference statements)
12
110
1
3
Order By: Relevance
“…Another possibility is that the increased risk is mediated by increases in overweight (32). In line with previous studies on type 2 diabetes (1,3,5,7,8), the observed positive association remained after adjustment for BMI, possibly suggesting a direct adverse effect of sweetened beverage intake on glucose homeostasis. However, it could be that the BMI does not fully indicate the level of visceral fat, which is a predictor of type 2 diabetes (33).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Another possibility is that the increased risk is mediated by increases in overweight (32). In line with previous studies on type 2 diabetes (1,3,5,7,8), the observed positive association remained after adjustment for BMI, possibly suggesting a direct adverse effect of sweetened beverage intake on glucose homeostasis. However, it could be that the BMI does not fully indicate the level of visceral fat, which is a predictor of type 2 diabetes (33).…”
Section: Discussionsupporting
confidence: 85%
“…Sugar-sweetened beverage intake has been linked to increased risk of type 2 diabetes in numerous studies (1,2,3,4,5,6); the most recent meta-analysis found that the risk increases by 13% for an increment of each serving per day in intake (7). Suggested routes by which sugar-sweetened beverages may influence diabetes risk are through glycemic or insulinemic responses or by contributing to excessive energy intake (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…The InterAct consortium evaluated the association of the consumption of sweet beverages (juices and nectars, sugar-sweetened soft drinks and artificially sweetened soft drinks) with T2D incidence in European adults [48]. The investigators established a case-cohort study including 12,403 incident T2D cases and a stratified subcohort of 16,154 participants selected from eight European cohorts participating in the European Prospective Investigation into Cancer and Nutrition (EPIC) study.…”
Section: Scientific Evaluationmentioning
confidence: 99%
“…High intake of these foods is associated with the nutritional transition toward ever growing prevalences of overweight and obesity in children 2 , and obesity and diabetes in adults 3 . Associations between sugar intake from beverages and weight gain 4 , type 2 diabetes [5][6][7] , cardiovascular disease, and metabolic syndrome have been reported 8,9 .…”
Section: Introductionmentioning
confidence: 99%